2011
DOI: 10.1177/0022022111406026
|View full text |Cite
|
Sign up to set email alerts
|

Language Effects on Children’s Nonverbal Number Line Estimations

Abstract: The mental number line of children is usually assumed to be language-independent; however, this independency has not yet been studied. In this cross-cultural study, we examined the influence of language properties on a nonverbal version of the number line task in Italian- and German-speaking first graders. The essential difference between the two languages concerns the inversion property of most German multi-digit numbers (e.g., 48 → “eight-and-forty”), whereas in Italian number-words no inversion is found. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
76
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 75 publications
(84 citation statements)
references
References 22 publications
6
76
1
1
Order By: Relevance
“…This suggests that some activation of the numerical magnitude takes place, which in the case of a large interdigit distance prevents a reversal. At first sight, this seems to contradict the results by Helmreich et al (2011), who found that German-speaking children showed larger deviations when locating numbers with a larger interdigit distance on a number line, while these numbers were easier in our study. However, Helmreich et al (2011) argued that these larger deviations were probably due to the fact that the difference between the target number and its inverted number are larger, so if a number is misinterpreted, the deviation is larger.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This suggests that some activation of the numerical magnitude takes place, which in the case of a large interdigit distance prevents a reversal. At first sight, this seems to contradict the results by Helmreich et al (2011), who found that German-speaking children showed larger deviations when locating numbers with a larger interdigit distance on a number line, while these numbers were easier in our study. However, Helmreich et al (2011) argued that these larger deviations were probably due to the fact that the difference between the target number and its inverted number are larger, so if a number is misinterpreted, the deviation is larger.…”
Section: Discussioncontrasting
confidence: 99%
“…Austrian, German-speaking children were less accurate than Italian children in positioning numbers with a large interdigit distance on a number line, while there was no difference for numbers with a small interdigit distance (Helmreich et al, 2011). Austrian children may have misinterpreted the numbers, e.g.…”
Section: Explaining Transcoding Item Difficultymentioning
confidence: 93%
“…They also noted that performance differences were more pronounced on the 0-100 number line than on the 0-20 number line. Similar findings were reported between German-and Italian-speaking children (Helmreich et al, 2011). The German counting system includes inversion properties (e.g., 48 is spoken as "eight and forty) whereas no such properties appear in Italian.…”
supporting
confidence: 84%
“…Accordingly, a cross-cultural study found that Italian speaking 1 st graders had higher accuracy in number line estimation task performance compared to German speaking 1 st graders. The difference between the two languages is the unique inversion property of German multi-digit numbers (e.g., 48 → "eight-and-forty") (Helmreich et al, 2011). This result demonstrated that number line estimation task performance can be influenced by the phonological-orthographic relation of language.…”
Section: Multiple Arithmetic Abilitiesmentioning
confidence: 81%